DISIPLIN KERJA DAN PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PD. DS PUTRA SUKAKERTA KABUPATEN CIAMIS - Hanna Diana Azizzah; Yayan Rudianto; Ridwan Hakiki; Erna Rusmiwati Sukandar (Journal of Innovation Research and Knowledge, 2024)
The work productivity of employees at PD. DS Putra Sukakerta has not achieved production results according to the set target. This is thought to be due to the application of work discipline that is not maximized so that in the production process there are still employees who have not obeyed the company's work rules. This research was conducted to determine the magnitude of the influence of work discipline to employee work productivity at PD. DS Putra Sukakerta, Ciamis Regency. The approach used in this research is quantitative descriptive with the nature of the research being replicative. The sample in this research amounted to 55 people. The analysis tool used is simple linear regression analysis. The results of this study indicate that employee work discipline at PD. DS Putra Sukakerta, Ciamis Regency is considered good as well as the employees work productivity at PD. DS Putra Sukakerta Ciamis Regency also shows result that is considered good. Based on the simple linear regression analysis calculation, the results shown that work discipline has a positive and significant influence to employee work productivity at PD. DS Putra Sukakerta, Ciamis Regency by 37,6%.